Contemporary issues in library and information science - Wan Mamat, Wan Ali (IIUM Press, 2011)
Knowledge has never been static. It constantly develops and expands, from one stage to another due to the ever inquiring human mind bestowed by Allah(S.W.T). In recent years, information explosion has been very profound, to the extent that librarianship in the traditional sense can no longer cope with the issues of servicing the ever expanding knowledge explosion. Fortunately, the development of information and communication technology (ICT) contributed immensely toward overcoming the issues of librarianship. With the development, so many recent issues relating to library and information science need to be studied and understood, especially by librarians and information scientists. The publication of this book is a step in the right direction toward promoting understanding on the ever expanding fields of librarianship and information science.